Program Standardisasi Guru dalam Meningkatkan Pendidikan Karakter Siswa di MI Takkal Denpasar Tahun Pelajaran 2019/2020 - Riana, Nadziri; Mahrusun, Mahrusun; Fawaid, M. (Faidatuna, 2022)
Character Education of students in an educational institution today is often neglected because of the impact of technology and lack of supervision by parents and teachers. One of the successes in improving the character education of students is determined by the existence of standardized teachers who have competence through the teacher standardization process. This is what underlies the conduct of research at MI Tawakkal Denpasar Bali which has students whose learning achievement is quite good. The research objectives in this thesis were to determine the implementation of the teacher standardization program at MI Tawakkal, to find out the teacher standardization program in improving the character education of MI Tawakkal students, and to find out the obstacles faced and solutions made in improving the character education of MI Tawakkal students. This type of research is descriptive with a qualitative approach with three data collection techniques, namely: observation, documentation, and interviews. The results of the study reveal that: The teacher standardization program at MI Tawakkal is running well because it is guided by the rules set by foundations and institutions, the Teacher Standardization Program produces quality teachers according to teacher competency standards, so as to improve student learning and character education, and factors. the obstacle is the family that does not fully play a role in implementing character education at home, the negative influence of social media, and the negative environment.